A hand-list of the birds of the Philippine islands. - McGregor, Richard C. (Richard Crittenden), 1871-1936 (Manila, Philippines Bureau of Printing, 1906)
Philippine Islands. Bureau of government laboratories. [Publication] no. 36
Keywords: Birds--Philippines.